Communicative-Functional Aspect of Vocatives in Rhetorical Discourse - Seitjanov, Zhetkerbay (The Lingua Spectrum, 2025)
This article examines the communicative-functional aspects of vocatives (“undalmalar”) in rhetorical discourse. Drawing on a mixed-methods approach—combining qualitative discourse analysis and quantitative frequency measures—the study analyzes over 200 instances of vocatives in political speeches and media texts. It integrates theoretical frameworks from pragmatics and discourse analysis (Karimov, 2019; Mirzaev & Tursunov, 2021) with findings from recent Uzbek scholarship (Ismoilova, 2022; Salimov, 2023) and comparative insights from The Lingua Spectrum (Urazmetova, 2024). The article identifies key patterns of address, attention-getting, and persuasive strategies, emphasizing how vocatives construct speaker–audience relations and contribute to rhetorical effectiveness within Karakalpak and broader Turkic linguistic traditions. Implications for translation studies, intercultural communication, and rhetorical pedagogy are discussed, offering practical recommendations for educators and translators. Ultimately, this research fills a gap in Karakalpak linguistics by systematically addressing the pragmatic dimensions of address forms and paving the way for future discourse studies.